Difficulties of using digital technology and their relationship to the quality of vocational performance among teachers and counselors - AlOmoush, Reem AbdElkareem; Al-tarawneh, Abdallah M A; Alhossan, Somaia Mouneeb; Altabeeb, Najah Abdulmajid Khalleefah; Tarawneh, Amany Wahed (Journal of Education and e-Learning Research, 2025)
This study aims to identify the difficulties of using digital technology and their relationship to the quality of vocational performance among teachers and counselors. The study sample consisted of 219 teachers and 132 counselors. To examine this, the researchers created a scale for measuring digital difficulties and another one for measuring the quality of vocational performance. The findings revealed no significant differences in the level of challenges with digital technology usage among teachers and counselors when considering variables such as gender and years of experience. There were no statistically significant differences in the quality of vocational performance of teachers based on gender; however, differences were found when considering the variable of years of experience. Conversely, there were no significant differences in the quality of vocational performance of counselors with respect to gender and years of experience. Furthermore, a significant inverse relationship was discovered between the challenges of employing digital technology and the quality of vocational performance among both teachers and counselors. The study recommended using and developing innovative educational methods and programs to meet the needs of teachers and counselors, which ultimately address the educational and psychological needs of students in line with the requirements of the digital age.